Evaluasi Pengaruh Autonomous Maintenance terhadap Kinerja Mesin Bubut dalam Penerapan Total Productive Maintenance di PT XYZ - Adinda Putri Bidari; Suseno Suseno (Pusat Riset dan Inovasi Nasional, 2025)
Competition in the manufacturing industry will encourage companies to make continuous improvements on the production floor, to maintain machine performance in order to minimize the breakdown value that occurs. As in the production process at PT XYZ felt a decrease in the performance of the lathe, the lathe that operated for 5 working hours sometimes, in the middle of the production process experienced downtime to breakdowns, as is known from February 24, 2024 to February 27, 2024, obstacles were faced during the production process where the machine experienced obstacles until it stopped completely and repeated for 3 consecutive days. Initial measurements have been made using Overall Equipment Effectivenes and Six Big Losses, which gave the result that the Availability value of the lathe reached 88.97%, the performance value was known to be at a percentage of 98.07%, while for Quality is at a percentage of 93.81%, and it is also known that the results of the Six Big Losses Analysis show that the factors that affect engine effectiveness are reduced speed losses, defect losses and breakdown losses. Therefore, improvements were made using the Total Productive Maintenance pillar, namely Autonomous Maintenance, which was developed using the 5S method which resulted in an increase in the availability value to 90.36%, performance to 87.57% and Quality to 99.02%.